IMPLEMENTASI MARKETPLACE DIGITAL “NITI” BERBASIS WEB SEBAGAI SARANA PROMOSI GAME KARYA ANAK BANGSA - Muhammad Hijrah Hamdallah Hijrah Hamdallah; Ghina Soraya Herlambang; casmadi yohanes (Universitas Logistik dan Bisnis Internasional, 2026)
The local game industry in Indonesia has significant potential, yet it still faces challenges in terms of promotion and distribution. Many local developers experience difficulties in showcasing their products because existing platforms are predominantly dominated by foreign companies. Therefore, this report discusses the design of a web-based digital marketplace named NITI, which is specifically developed to support games created by Indonesian developers. The system development was carried out through needs analysis, database design using an Entity Relationship Diagram (ERD), and system implementation based on PHP and MySQL. The NITI platform provides main features such as game product management, transaction and order management systems, community chat, and a revenue- sharing mechanism between developers and the platform. In addition, administrators play a role in managing data and monitoring system activities. The results of the design indicate that NITI can help increase the visibility of local games, facilitate the monetization process, and build a more structured and sustainable game industry ecosystem.